Yo puedo segundos pasos - Silvaggio-Adams, Elizabeth; Vallejo-Alegre, Rocío (Open textbook library., 2021)
Perhaps you remembered what the title of your book means from your previous experiences with Spanish. That is a great start! As you begin the equivalent of a second semester Spanish course with these materials, some of you might think about how long it has been since you studied Spanish while others may come to the class with some background knowledge. We want you to know this book has been designed with many types of learners in mind. Our goals were to address the need for students to achieve the ability to communicate in written and spoken form. We sought to address a common statement by students that may have previous experiences, be they from secondary school or another college that say, “I have studied Spanish for years and don’t know how to speak or write it.” We also sought to present a reasonable alternative to the expensive textbooks and online packages that don’t seem to be practical or relevant. We sought to enhance second language learning by creating our own materials that take a new approach, the flipped classroom model, to learning a second language based upon the skills that we deem most useful and that will enable our students to confidently express themselves in Spanish–tú puedes con Yo puedo 2.